THE ANALYSIS OF DELAY IMPLEMENTATION RISK SPATIAL BALANCE INTEGRATION MAPPING PROJECT IN THE CILIWUNG-CISADANE RIVER AREA - Yudi Firmansyah; Pio Ranap Tua Naibaho (International Journal of Multidisciplinary Research and Literature, 2023)
Consulting Service jobs often have high complexity; only some of these jobs experience delays in completion. The delay has a significant impact on both the employer and the party that is responsible for carrying out the activity. The uncertainty extremely influences both of these parties. In this study, an examination of the factors that carry a high potential for resulting in delays in the completion of activities is carried out. This investigation classified risk factors into one of three categories according to the implementation stage. They are variable components of support for the implementation of work, technical implementation of work, and assistance/supervision of activities. Factors with a high level of risk are then responded to with a risk response as a step to follow up on these risk factors. As for minimizing risk, the Risk Reduction method is used